Changes in macrophage function modulated by the lipid environment. Issue 3 (April 2016) - Williams, Michael R; Cauvi, David M; Rivera, Isabel; Hawisher, Dennis; De Maio, Antonio
Macrophages (Mφs) play a critical role in the defense against pathogens, orchestrating the inflammatory response during injury and maintaining tissue homeostasis. During these processes, macrophages encounter a variety of environmental conditions that are likely to change their gene expression pattern, which modulates their function. In this study, we found that murine Mφs displayed two different subpopulations characterized by differences in morphologies, expression of surface markers and phagocytic capacity under non-stimulated conditions. These two subpopulations could be recapitulated by changes in the culture conditions. Thus, Mφs grown in suspension in the presence of serum were highly phagocytic, whereas subtraction of serum resulted in rapid attachment and reduced phagocytic activity. The difference in phagocytosis between these subpopulations was correlated with the expression levels of FcγR. These two cell subpopulations also differed in their responses to LPS and the expression of surface markers, including CD14, CD86, scavenger receptor A1, TLR4 and low-density lipoprotein receptor. Moreover, we found that the lipid/cholesterol content in the culture medium mediated the differences between these two cell subpopulations. Thus, we described a mechanism that modulates Mφ function depending on the exposure to lipids within their surrounding microenvironment.